Gender Differences in Travel Behavior, for Daily Trips in Kathmandu Valley - Bajracharya, Ashim Ratna; Shrestha, Sudha; Bhatta, Kishan Datta (Journal of Engineering Technology and Planning, 2022)
Kathmandu valley is the main center for economic activities and with it travel demand has increased drastically in the Valley in the recent years, along with rapid growth in population. This paper brings into highlight, the role of gender on urban mobility, for daily trips, by assessing the gender differences in travel behavior of workers and students, in commuting their work and educational trips respectively. Household survey was carried out in different parts of the study area, using random sampling. Data was analyzed to associate gender with travel mode choice and trip length. The statistical analysis of the travel data shows that there is a significant level of association between gender and the way, they travel. The modal share and trip length varies significantly between men and women, more prominently for work trips. For educational trips, the variation is observed comparatively, to a lesser extent. For work trips, men are using more of the private vehicles and relying less on public transport and non-motorized means of travel, as compared to women. It is also revealed that that males are commuting longer trip distances as compared to females. From the findings, recommendations for gender equality in urban transport and promotion of sustainable urban mobility, emphasizing the use of public transport and non-motorized modes of transport.